2017
DOI: 10.1093/jxb/erx060
|View full text |Cite
|
Sign up to set email alerts
|

Flagellin peptide flg22 gains access to long-distance trafficking in Arabidopsis via its receptor, FLS2

Abstract: HighlightReceptor-mediated endocytosis enables flg22 internalization, trafficking to vacuoles, entry to vasculature and mobilization to distal tissues. Receptors can function similarly to transporters and allow uptake and long-distance transport of molecules.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
21
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(27 citation statements)
references
References 73 publications
2
21
0
Order By: Relevance
“…This difference may result from different electrical charges in the three peptides, as CLE26 has one more arginine than CLE25, and CLE45 has two more arginines than CLE25. We also cannot rule out other mechanisms, such as specific membrane transport, which may contribute to different transport patterns (Botha et al ., ; Jelenska et al ., ).…”
Section: Discussionmentioning
confidence: 97%
“…This difference may result from different electrical charges in the three peptides, as CLE26 has one more arginine than CLE25, and CLE45 has two more arginines than CLE25. We also cannot rule out other mechanisms, such as specific membrane transport, which may contribute to different transport patterns (Botha et al ., ; Jelenska et al ., ).…”
Section: Discussionmentioning
confidence: 97%
“…The flg22 bacterial peptide was also able to reduce stomatal development in our experiments. Recent evidence shows that flg22 is itself potentially mobile (Jelenska, Davern, Standaert, Mirzadeh, & Greenberg, ), but its effect in distal tissues remains unknown and was not explored here. Instead, by studying Arabidopsis genotypes with defects in defence responses and by applying chemical defence elicitors, we have shown that the FLS2 flagellin receptor, SA production, and the AZI1 protein are most probably required to perceive the bacterial stress signal and to generate and/or perceive a yet unknown systemic developmental signal (Figures and ).…”
Section: Discussionmentioning
confidence: 99%
“…Another LRR-RLK receptor, FLAGELLIN SENSING 2 (FLS2), is involved in recognising MAMP and binds to flg22, which is a 22-amino-acid peptide that is present in the N-terminal part of a flagellin. Recognising flg22 leads to rapid extracellular alkalisation, ROS production, the activation of a mitogen-activated protein kinase (MAPK) cascade and the upregulation of pathogenesis-related genes in A. thaliana [104,105]. flg22 from the rhizobacterium B. phytofirmans had weak elicitory activity on grapevine but a potent activity on A. thaliana .…”
Section: Plant Genetic Features That Are Involved In Interactions mentioning
confidence: 99%